"Side‐Product Catalysis": Substrate Autoxidation as an Overlooked Side Reaction Generating a Co‐Catalyst for Enhancing Asymmetric Aldol Reactions. Issue 8 (30th March 2017) - Heidlindemann, Marcel; Berkessel, Albrecht; Gröger, Harald
Abstract: An acid formed autoxidatively from an aldehyde substrate as a side product was found to alter the reaction kinetics and selectivity significantly in the direct asymmetric aldol reaction between an aldehyde and acetone, both in aqueous media and cyclohexane. Furthermore, this side‐product catalysis ("impurity catalysis") was also observed upon using commercial samples of aldehydes without purification prior to their use (owing to the presence of the acid formed therein during storage), which thus underlines the impact of substrate purity on the reaction course of the catalytic process. Abstract : Helpful side‐products : An acid formed autoxidatively from an aldehyde substrate significantly alters the reaction kinetics and selectivity in the direct asymmetric aldol reaction between an aldehyde and acetone, both in aqueous media and cyclohexane. This "side‐product catalysis" is also observed upon using commercial aldehyde samples without purification prior to their use, which thus underlines the impact of substrate purity.